Regulation of fruit development by pollen in the Omani date palm - Dietz, Toni Herbert (1998)
Effects of various pollen types on the fruit growth and development in two maternal cultivars of Omani Date Palm were studied in the Northern Batinah region of the Sultanate Oman. Discrete stages in the development were identified, quantified and examined with regard to important variables including fruit set, weight, size, maturity, chemical composition, appearance and yield. Procedures were developed to compare across the different maternal cultivars and temperature environments. The pollen types were distinct in their effects, particularly as regards weight, time to maturity, ripening, sugar content, appearance and yield of certain consumable fruit stages. These effects were influenced by the female type and differential fruit set. True metaxenic and xenic effects were evidenced by excluding influences of fruit set. These were on fruit fresh weight, size, maturity and ripening in cv Khasab in 1996 and 1995 and in cv Khalas in 1996. Differences in cv Khalas in 1995 were due to differences in fruit set. Pollen effects could be measured in cv Khalas throughout fruit development, while they appeared in cv Khasab only in the later stages. Khori consistently induced the highest mature fruit fresh weight (14.8 g in cv Khalas, 13.0 g in cv Khasab) compared to Bahlani (12.6 g and 12.3 g, respectively and AI Arudsabba (12.2 9 and 11.1 g, respectively). However, differences in fruit set between pollen blocks in cv Khalas in 1995 caused the largest ripe fruit fresh weight (16.1 g) in the AI Arudsabba block compared to Bahlani (14.1 g) and Khori (13.4 g). The effect of high fruit set (initial set was 49 % with Khori and 34 % with AI Arudsabba) in masking and modifying pollen effects was evident because AI Arudsabba induced about 40 % less fruit fresh weight than Khori in the initial stages of development. The response to applications of plant growth regulators was specific to the pollen type used. GA increased, by about 100 %, fruit fresh weight in AI Arudsabba pollinated Khalas fruits but reduced it to about 50 % in Khon pollinated ones. NAA caused the abscission of all unfertilized ovaries in Khon pollinated Khalas but not in those pollinated with AI Arudsabba. In the absence of syngamy physiological rather than hereditary causes were implied. Correlations between fruit set and fruit fresh weight did not exist in the early stages suggesting that the observed pollen effects were truly metaxenic or xenic. In the later stages clear and consistent negative correlations existed for the AI Arudsabba block. Probably in the other pollen blocks some mechanism compensated this control of one variable over the other. Late correlations for the Khori block in cv Khalas suggested that high fruit fresh weight induced fruit drop. The absence of pollen effects on late correlations in cv Khasab implied a genetic cause. The strong influence of fruit set on ripening (% ripe fruits) in Khori pOllinated bunches indicated a specifically strong influence exerted by fruit set over ripening. Time to physiological maturity was affected by pollen type only in cv Khalas where AI Arudsabba and Bahlani induced earlier maturity (7 days) than Khori. Khori pollinated fruits appeared to mature later in both female cvs except cv Khalas in 1995. Bahlani induced earlier maturity in both female cvs. Regression analysis between thermal time and fruit fresh weight provided evidence for the effects specific to Khori. As Bahlani induced the same early maturity in both female cvs. Ripening was most uniform in Bahlani pollinated bunches, but faster in Khori pollinated ones. Correlations of thermal time and ripeness indicated that the temperature regime has a strong influence (r=0.99) over ripening in Bahlani pollinated bunches. Early pollen effects were probably due to physiological mechanisms, probably hormonal activity, which could be attributed to pollen type and pollination. Late effects were under the influence of male x female interactions and were thought to be genetic. Bahlani consistently induced the highest fruit fresh weight and size in the early fruit stages, but Khori in the later stages. Only in cv Khasab was Bahlani in the later stages on par with Khori in this regard. The situation was similar for fruit and seed size. Compositional differences between pollen types were not reflected in those between the ovaries one day after pollination with different male types. This largely precluded the possibility that the early growth response was directly due to the mere addition of substances contributed by the pollen grains. Preliminary investigations indicated that pollen types were a priori distinct with regard to their biochemical composition and mineral content in that AI Arudsabba and Bahlani were similar and differed from Khori. Khori's pollen grains were largest (22 mum, less than 20 mum in other types) and its pollen tube growth the most uniform (CV 56% compared to 80-110% with other types), while Bahlani had the most vigorous pollen tube growth (tube length up to 220 JlI1lI24h). Khori contained more growth promoters, possibly GA , than AI Arudsabba. Khori brought about relatively stable bunch yields in cv Khalas (11 kg in 1996, 15 kg in 1995) and large (about 4 cm long), heavy and sweet fruits, but delayed maturity of the fruits (7days in cv Khalas). AI Arudsabba produced a slightly higher cumulative yield (28 kg) of similar yield stability, but produced fruits of poor quality in regard to fruit size (about 3.5 cm in cv Khalas), fresh weight and a low total sugar content (less than 40% in Khalas, less than 50 % in Khasab). Bahlani had clear advantages, in that it induced sweet fruits, but produced the least stable yields of fruits (cv Khalas: 16 kg in 1996, 7 kg in 1995) with relatively low weight and small fruits.